Native house designing pattern recognition in Mazandaran province with climatic approach - Rood Posht, Azadeh Mahmoudi Kohneh; Daneshjoo, Khosro; Mofidi Shemirani, Seyed Majid (Nexo Revista Científica, 2020)
In Forming residential house in Khazar’s shore, climatic condition plays a basic role because in them had used of natural energy and environmental condition for heating, cooling and air conditioning.With studying, recognition and analyses of principles and patterns of native architecture can find out the compatibility of them with the climatic condition. With appearing modern architecture and destroying construction identity, patternology is one of the important issues that wants to find the practical methods for accessing to identity maker elements and patterns of past and using of them in now a day modern architecture. Traditional residential texture as the fundamental core of cities and so elements and architecture construction in them undoubtedly are worthy heritage for studying and analyzing and presenting proper patterns of native architecture. In this study first with an analyzing- descriptive approach have an overview and then the skeletal factors affecting texture and traditional residential constructions of Mazandaran province patternology are identified. Study method in this method is analyzing-descriptive and used of fieldwork for fundamental recognition and identifying for sample structures that are under studying. Finally, due to the obtained results, principles of native architecture and comparison of available criteria, native house designing patterns will present.